2019
DOI: 10.1186/s40249-019-0554-4
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of drug resistance tuberculosis based on reference laboratory data in Ethiopia

Abstract: Background Both passive and active surveillance of drug resistance have an important role in tuberculosis (TB) control program. Surveillance data are important to estimate the magnitude of drug resistance TB, to know the trend of the disease, assess the performance of the program, and to forecast diagnosis and treatment supplies. Therefore, this study aimed to determine the prevalence and the proportion of drug resistant tuberculosis in Ethiopia based on passively collected data. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 18 publications
1
27
2
Order By: Relevance
“…The proportion of MDR among new cases of the present study was 41 (1.8%) while among previously admitted cases were 159 (6.8%). Similar studies elsewhere in Ethiopia revealed that the proportion of MDR-TB was 4.3% in new patients and 6.7% in previously treated patients [21], 2.18% in newly diagnosed and 21.07% and previously treated patients [22], 2% of new cases and 17% among previously treated patients [23], 2.3% among new cases and 13.9 % among previously treated cases [24] and 2.3% among new and 17.8% among previously treated patients [25]. It is to be noted that 20 years ago, reports showed that the prevalence of MDR-TB was almost nil or 1% in different parts of Ethiopia [26].…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of MDR among new cases of the present study was 41 (1.8%) while among previously admitted cases were 159 (6.8%). Similar studies elsewhere in Ethiopia revealed that the proportion of MDR-TB was 4.3% in new patients and 6.7% in previously treated patients [21], 2.18% in newly diagnosed and 21.07% and previously treated patients [22], 2% of new cases and 17% among previously treated patients [23], 2.3% among new cases and 13.9 % among previously treated cases [24] and 2.3% among new and 17.8% among previously treated patients [25]. It is to be noted that 20 years ago, reports showed that the prevalence of MDR-TB was almost nil or 1% in different parts of Ethiopia [26].…”
Section: Discussionsupporting
confidence: 80%
“…The highest monoresistance to INH drug from newly diagnosed PTB patients were reported from different parts of the country [ 7 9 ]. In a retrospective study, a relatively similar INH mono resistance was reported from the National Tuberculosis Reference Laboratory and the seven Regional Laboratories in Ethiopia [ 24 ]. The relatively high proportion of INH resistance compared with RIF in our study could be due to the common use of INH for a longer time because it is cheap, effective and has a lower rate of adverse events [ 25 ].…”
Section: Discussionmentioning
confidence: 78%
“…However, our result was in line with previous studies in our country [ 8 , 9 , 30 , 31 ]. High MDR-TB (4.3%) prevalence was reported from the National Tuberculosis Reference Laboratory and the seven Regional Laboratories among newly diagnosed TB patients [ 24 ]. This may be due to variation in sample size and studied population.…”
Section: Discussionmentioning
confidence: 99%
“…The crisis of DR-TB progressively jeopardizes the TB control program in Ethiopia. Based on the 2017/2018 Ethiopian national TB reference laboratory data, the proportion of Multidrug-Resistant Tuberculosis (MDR-TB) was 11.6% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%